Elements of argumentation - Besnard, Philippe, 1958-; Hunter, Anthony, 1962- (Cambridge, Mass. : MIT Press, 2008)
Here the authors introduce techniques for formalizing deductive argumentation in artificial intelligence, emphasising emerging formalizations for practical argumentation. They discuss how arguments can be constructed, how key intrinsic and extrinsic factors can be identified, and how these analyses can be harnessed in the real world.
Nature of argumentation -- Abstract argumentation -- Logical argumentation -- Practical argumentation -- Comparing and rationalizing arguments -- Considering the audience -- Algorithms for argumentation -- Comparison with relation approaches -- Future directions -- Table of uniform notation -- Review of trees -- Review of classical logic -- Proofs for results in book.
Includes bibliographical references (pages 285-293) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Artificial intelligence; Reasoning; Logic; Information technology; Electronic data processing; Intelligence artificielle; Technologie de l'information.; artificial intelligence; information technology; COMPUTERS -- Enterprise Applications -- Business Intelligence Tools; COMPUTERS -- Intelligence (AI) & Semantics; Electronic data processing; Artificial intelligence; Information technology; Logic; Reasoning; COMPUTER SCIENCE/Artificial Intelligence